Technology as portrayed in popular culture: an analysis of the film Her - Qaderi, Sophia (My University, 2021)
The internet has completely reconfigured social relationships. As information and communication technology continues to change and evolve in ways that were previously unimaginable, films like Spike Jonze’s Her seem not so far from future technological developments. The purpose of this paper is to depict how Jonze’s work does a substantive job in portraying the disconnection from the world individual undergoes when they overly depend on technology for affection and meaning. One may think the idea of an Artificial Intelligence (AI) becoming so personable as unachievable, however, most of our smart technology is already customized to suit our personal needs and gives us quick information such as Siri or Alexa. This paper discusses some relevant aspects of this problem.
Keywords: technology; social relationships